Penurunan Salinitas (Kadar Klorida) Artifisial Dengan Proses Pertukaran Ion (Ion Exchange) - Musyarrofah Musyarrofah; Muhammad Irfa'i; Abdul Khair (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2020)
Brackish water caused of high chloride sodium content, giving to feel briny at water. The only chemical process can remove chloride is the ion exchange. The aim of this study was to determine the difference of percentage decreasing of chloride levels in variations of chloride level in brackish water (870 mg/l, 1712 mg/l, 2501 mg/l) and variation of sampling time (1,5 hours, 3 hours, 4,5 hours). Brackish water used the result of dilution of brines using freshwater. This process brackish water by passing into a resin media tube’s diameter 5cm and 40cm high with flow discharge 100ml/min. The results of chloride levels after the process still exceeded the quality standard Permenkes RI No.492/MENKES/PER/IV/2010. The avarage chloride levels after from the chloride 870 mg/l is 776,7 mg/l, the chloride 1712 mg/l is 1520 mg/l and the chloride 2501 mg/l is 2139 mg/l. From Two-Way-Anova test showed a significant difference between the percentage of decreasing chloride levels in various sampling time, the variation of initial chloride level, and interaction between variation in initial chloride content and sampling time.